Особенности акустических измерений в прессовках на основе порошка титана - Безымянный, Юрий Георгиевич; Козирацкий, Евгений Александрович; Назаренко, Владимир Андреевич; Тесленко, Людмила Олеговна (НТУ "ХПИ", 2017)
В результате изучения закономерностей изменения параметров упругих волн, прошедших через образцы пористых прессовок, проведена адаптация методик измерений динамических характеристик упругости импульсным и резонансным методами к особенностям исследуемых материалов для повышения достоверности, точности и информативности измерений. Применение адаптированных методик позволило получить качественно новую информацию о закономерностях изменения скоростей распространения упругих волн как функции параметров структуры в прессовках на основе порошка титана. Показано, что зависимости скорости распространения от пористости различны на разных участках и для разных типов волн. При этом участки отделены аномальной зоной пористости.

As a result of studying the regularities of the changes in the parameters of elastic waves passed through samples of porous compacts, the methods of measuring the dynamic characteristics of elasticity by pulse and resonant methods have been adapted to the features of the materials under study to increase the reliability, accuracy, and informativeness of the measurements. The use of adapted techniques allowed obtaining qualitatively new information about the regularities of the variation of the elastic wave propagation as a function of the structure parameters in compacts based on titanium powder. The paper presents the results of pulsed and resonant methods used to study the characteristics of porous titanium. A technique is proposed for estimating the correctness of the results obtained. It is shown that the dependence of the propagation velocity on the porosity is different at different sites and for different types of waves. The sections are separated by an abnormal zone of porosity.
Features of acoustic measurements in compacts based on titanium powder
Keywords: неразрушающий контроль; акустические методы; скорость ультразвука; пористые прессовки; скорость распространения; СР; импульсный метод; non-destructive testing; acoustic methods; ultrasound speed